Role of Tissue-Type Plasminogen Activator in Ischemic Stroke - Yasuhiro Suzuki (Elsevier, 2010)
Tissue-type plasminogen activator (t-PA) administration has been approved for treating acute ischemic stroke, but delayed treatment is associated with increased risk of cerebral hemorrhage and brain injury. t-PA, a serine proteinase, converts plasminogen to plasmin. Plasmin participates not only in the degradation of fibrin, causing clot lysis, but also in the degradation of various extracellular matrix proteins, either directly or via the activation of matrix metalloproteinase (MMPs). We established an animal stroke model and observed a phenomenon of spontaneous rethrombosis and thrombolysis in the cerebral vessels after vessel damage. Endogenous t-PA protected brain damage by recanalization, but the protective effect deteriorated when the occluded vessels were not reopened. On studying intracranial hemorrhage (ICH) induced by t-PA treatment of ischemic stroke, we observed that MMP-3 is relatively important for the enhanced ICH induced by t-PA. MMP-3 was upregulated by t-PA in endothelial cells, but the upregulation was prevented by the inhibition of either low-density lipoprotein receptor-related protein (LRP) or nuclear factor kappa-B (NF-κB) activation. Thus, t-PA causes ICH via MMP-3 induction in endothelial cells, which is regulated through the LRP/NF-κB pathway, and could be targeted to improve the therapeutic efficacy of t-PA for acute ischemic stroke. Keywords:: tissue-type plasminogen activator, cerebral ischemia, intracranial hemorrhage, matrix metalloproteinase, low-density lipoprotein receptor-related protein